Residual stress release and corresponding microstructural changes in high-energy impact-modified GH4169 after aging at 425 °C and 650 °C - Qiang Wang; Shixiang Shuai; Guoxin Lu; Bonnie Attard; Rongyao Ma; Shuang Gao; Arif Rochman; Glenn Cassar (Journal of Materials Research and Technology)
The nickel-based superalloy is a critical material in aero-engines, where enhanced durability and resistance to stress relaxation are essential. This study evaluates the effectiveness of a high-energy composite modification technique, applied through dual surface friction methods, to induce residual stress and examines the stability of this stress under medium-temperature aging conditions. GH4169 was selected and a foundational study was conducted to quantify residual stress relaxation under medium-temperature aging treatment. The surface strengthening method used was a high-energy composite modification known for its significant post-treatment effects. The specific temperatures for medium-temperature aging treatment were 425 °C and 650 °C. The test results of the residual stress field confirmed the phenomenon of residual stress relaxation under the influence of temperature. Correspondingly, the different degrees of stress relaxation caused by varying aging treatment conditions are closely related to the microstructural changes within the material. Areas with a higher number of annealing twins exhibited a more pronounced degree of residual stress relaxation. By elucidating the link between stress relaxation and microstructural changes, this research offers a theoretical foundation for optimizing surface-strengthening processes and setting optimal operational temperatures for advanced structural materials.